Metody określania struktury emulsji O/W wytwarzanych w rozpylaczach o stożkowej komorze wirowej = The methods for determining the structure of O/W emulsion formed in the atomizers with conical swirl chamber - Włodarczak, Sylwia; Ochowiak, Marek; Krupińska, Andżelika; Markowska, Małgorzata (Zielona Góra: Uniwersytet Zielonogórski, Instytut Metrologii, Elektroniki i Informatyki)
The paper presents the process of emulsion O/W formation in the pressure-swirl atomizers of the different construction. Two methods for determining the droplet size are discussed in detail. Droplet size distributions and Sauter mean diameters were analyzed. It has been shown that the oil phase share and atomizer geometry, especially the chamber height, affect the droplet size.
Keywords: komputeryzacja; przyrządy pomiarowe; informatyka; technologie informacyjne